In the Period 1998-2018 Analysis of the Investment Made in Tourism and Economic Growth with Granger Causality and Toda-Yamamoto Method in Turkey - Kambur, Emine; Aksoy, Müjde (Fırat University, 2022)
The expectation that the investments made in the tourism industry of developing countries such as Turkey will increase economic growth has increased the interest in research on this subject. Because the increase in Turkey's growth rate has created a motivating situation for investments in the tourism industry. This article deals with the causality relations between investments in tourism and GDP in Turkey in 1998 and later, within the framework of a Vector Autoregressive Model (VAR) using 12-month data. Granger causality and Toda-Yamamoto causality estimations have been preferred as method. According to Granger causality test results, inward investments made in tourism is a cause of economic growth. However, economic growth isn’t a cause of inward investments made in tourism in Turkey. According to Toda-Yamamoto method, inward investments made in tourism is a cause of economic growth, but, economic growth is not a cause of inward investments made in tourism in Turkey. The results of both methods are similar with each other. In this study, it has been determined that tourism investments have a positive effect on Turkey's economic growth and development. Within the scope of this information, various policy recommendations have been produced in the conclusion section.

Türkiye gibi gelişmekte olan ülkelerde turizm endüstrisine yapılan yatırımların, ekonomik büyümeyi artıracağı beklentisi bu konuda yapılan araştırmalara yönelik ilgiyi artırmıştır. Çünkü Türkiye’nin büyüme hızındaki artış, turizm endüstrisine yapılan yatırımlar için motive edici bir durumu ortaya çıkarmıştır. Bu çalışma Türkiye’de 1998 ve sonrası yirmi yıllık dönemde turizme yapılan yatırımlar ve GSYH arasındaki nedensellik ilişkilerini yıllık veriler kullanarak bir Vektör Otoregresif Model (VAR) çerçevesinde ele almaktadır. Yöntem olarak Granger nedensellik ve Toda-Yamamoto nedensellik tahminleri kullanılmıştır. Granger nedensellik testi sonucuna göre, Türkiye’de turizme yapılan iç yatırımlar ekonomik büyümenin bir nedenidir. Ancak ekonomik büyüme Türkiye’de turizme yapılan iç yatırımların bir nedeni değildir. Toda-Yamamoto yöntemine göre de Türkiye’de turizme yapılan iç yatırımlar ekonomik büyümenin bir nedenidir. Fakat ekonomik büyüme, turizme yapılan iç yatırımların nedeni değildir. Her iki yöntemin sonuçları birbiri ile benzeşmektedir. Türkiye için ele alınan bu çalışmada turizme yapılan yatırımların ekonomik büyümeyi ve gelişmeyi olumlu yönde etkilediği ortaya konulmuştur. Bu bilgiler kapsamında sonuç kısmında çeşitli politika önerileri üretilmiştir.
1998-2018 DÖNEMİNDE TÜRKİYE’DE TURİZME YAPILAN YATIRIM İLE EKONOMİK BÜYÜME İLİŞKİSİNİN GRANGER NEDENSELLİK VE TODA-YAMAMOTO YÖNTEMLERİ İLE ANALİZİ